AB0450 Impact of therapeutic patient education on safety skills and infectious events of patients treated by biological dmards in rheumatology: a bi-centric study. (12th June 2018) - Frantzen, L.; Ardizzone, M.; Sparsa, L.; Oréfice, D.; Afif, N.; Arnaud, L.; Gottenberg, J.-E.; Sibilia, J.; Sordet, C.
Abstract : Background: Patients treated with biologic DMARDs have to be aware of the specific adverse events and have to be able to manage their treatments in case of infectious disease. Therapeutic Patient Education aims to enable patient to acquire these safety skills. Objectives: To assess the impact of Therapeutic Patient Education on safety skills and management of infectious events in patients treated with biologic DMARDs in rheumatology. Methods: Bi-centric analytical study comparing safety skills and infectious events between two cohorts of patients (TPE and TPE-naive). Safety skills were assessed by an auto-assessment called "Biosecure", rated on a scale from 0 to 100. This assessment explores several dimensions of treatment management and was validated for assessment of safety skills in patients treated with biologic DMARDs in rheumatology in a preliminary study. Infectious events and their management were self-reported by patients. A cluster analysis aimed to separate patients into working group based on their shortcomings (on the basis of their answers to the Biosecure Assessment). Results: 414 patients answered the assessment. The median Biosecure Score was 70.98/100 (Q1Q3: 60.97–84.63) 47% attended Therapeutic Patient Education. The median Biosecure Score was significantly higher in the TPE group than in the TPE-naive group (74.88 versus 67.20/100; p<0.05). Regarding the observance to treatment, activity scores, vaccination rates onf incidence of infectious events, there were no significant difference between the groups TPE and TPE-naive. Nevertheless, there were more treatment interruption for infectious events in the TPE group, suggesting that TPE could lead to better management of treatment during infectious events. Cluster analysis based on Biosecure assessment separated patients into 3 level groups but failed to identify specific patient profiles. Conclusions: Therapeutic Patient Education could provide better safety skills and better treatment management in patients treated with biologic DMARDs in rheumatology. Prospective studies may confirm the impact of TPE on treatment management during infectious events. Further studies may assess the impact of TPE on incidence of serious infectious events. References: [1] Orefice D, Beauvais C, Gossec L, Flipon E, Fautrel B, Marguerie L, et al. Cross-sectional study of self-care safety skills in 677 patients on biodrugs for inflammatory joint disease. Jt Bone Spine Rev Rhum. déc 2014;81(6):502. [2] Rat A-C, Fautrel B, Flipon E, Gossec L, Marguerie L, Nataf H, et al. Factors associated with knowledge and safety skills of arthritis patients receiving biologics: A survey of 677 patients. Joint Bone Spine. Disclosure of Interest: None declared